North Africa's Menace AQIM's Evolution and the U.S. Policy Response - Chivvis, Christopher S. (RAND Corporation, 2013)
This report assesses the threat from the North African terrorist organization Al Qaeda in the Islamic Maghreb (AQIM). AQIM is a serious regional problem, but its similarity to the Al Qaeda of Osama Bin Laden should not be exaggerated. AQIM does not currently seem bent on global jihad. In most situations, the wisest policy responses to the AQIM threat will focus on supporting local actors and U.S. allies in Europe.